Analisis Respon Peserta Didik Terhadap Penguatan Literasi dalam Pembelajaran IPAS Berdiferensiasi di Sekolah Dasar - Erika Maulita Zuliyawati; Ani Setiya Agustin (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
This research aims to describe students’ responses to strengthening literacy in differentiated Natural and Social Sciences learning. The research method used is qualitative with a case study approach. Data collection was carried out through interviews, observation and documentation, as well as questionnaires filled out by students. Research findings show that differentiated science and science learning by strengthening literacy has a positive impact on students. Students show active participation and high enthusiasm for learning during learning activities. Using different storybooks for each group helps strengthen students’ literacy. The students also responded positively to the activities of discussing and working together in groups. Support and guidance from teachers in strengthening literacy is considered to really help students in understanding the material. Student learning outcomes have also increased. Overall, the differentiated approach by strengthening literacy in science and science learning is considered fun and effective by students. The conclusion is that this approach can create a pleasant learning environment and optimize the visual, auditory and kinesthetic learning styles of each student to achieve optimal learning potential.